Caracterização molecular, avaliação do perfil de susceptibilidade a antifúngicos e formação de biofilme de isolados clínicos pertencentes ao complexo Candida haemulonii e Candida auris - Lima, Soraia Lopes [UNIFESP] (2017)
The Candida haemulonii complex (C. haemulonii, C. haemulonii var. vulnera and C. duobushaemulonii) and the phylogenetically related species (C. auris and C. pseudohaemulonii) are agents of superficial and invasive mycoses, responsible for high rates of morbidity and mortality. The phenotypic methods are unable to correctly identify closely related species, such as that included in the C. haemulonii complex. It is essential to use molecular techniques for identification, and sequencing the ITS region of the ribosomal DNA is considered the gold standard method for Candida species identification. As these microorganisms can be found in hospital environments and have shown low susceptibility to antifungal agents, it is essential that more studies are performed to evaluate their biological characteristics. Objectives: (i) To identify clinical isolates stored at the Culture Collection of LEMI, identified as C. haemulonii (sensu lato) and C. auris by sequencing the ITS region of rDNA generating high quality sequences; (ii) To evaluate in vitro susceptibility profile of these isolates with 5 antifungal agents; (iii) To evaluate biofilm formation of C. haemulonii (sensu lato) isolates and related species. Material and methods: Sixty-six clinical isolates from different sites were selected from several medical centers from four Latin American countries from 2008 to 2016. For the molecular identification, ITS sequencing was performed and the sequences obtained were compared to those deposited in NCBI genomic database. Susceptibility tests with the antifungals fluconazole (FLC), voriconazole (VRC), anidulafungin (ANI), 5-fluorocytosine (5-FC) and amphotericin-B (AMB) were performed according to CLSI document M27-A3. For the biofilm assays, 96-well plates were used and biofilm quantification was performed by using violet crystal staining. Results: Among the 66 isolates studied, 37 were identified as C. auris, 11 as C. haemulonii var. vulnera, 9 as C. haemulonii (sensu stricto) and 9 as C. duobushaemuonii. No C. pseudohaemulonii isolates were found. Inter-specific variability of antifungal susceptibility was observed among four agents tested. The 4 species identified were resistant to AMB and FLC. Regarding VRC, lower MICs were obtained for the majority of C. haemulonii (sensu lato) isolates. 5-FC and ANI agents showed activity against the isolates tested. Regarding the biofilm formation, C. haemulonii (sensu stricto) and C. haemulonii var. vulnera were the species that showed higher intra-specific variability. The species that presented the highest and the lowest biofilm formation were C. auris and C. duobushaemulonii, respectively. Conclusions: The sequencing of ITS region allowed accurate identification of all isolates and generated high quality sequences. C. haemulonii complex and C. auris were resistant to AMB and FLC, but the majority of the isolates were susceptible to ANI and 5-FC. All species studied were able to form biofilm, especially C. auris, which presented the highest capability to produce biofilm.